Budget Deficit and Economic Growth in Nepal: ARDL Bound Test Analysis - Kshetri, Tilak; Adhikari, Shiva Raj; Thapa, Sanjeet Singh; Thapa-Parajuli, Resham (Economic Journal of Nepal, 2023)
Using budget deficit to grow real gross domestic product (RGDP) is an issue of perpetual economic debate with different theoretical traditions reaching divergent conclusions. Nepal has always had a budget deficit in its modern history, and the role of this deficit in the economy has not been adequately studied. This paper studies how the budget deficit affected economic growth in both short and long periods using the ARDL approach to the bound test. The paper shows that budget deficit positively impacts RGDP in the short-run, i.e., crowding-in effect as described by Keynesian tradition, but has no effect in the long-term supporting the Ricardian equivalence hypothesis. Further, the results show that exports are largely detached from the long-run RGDP despite having a role in short-run economic performance. Private gross capital formation is also important in short and long horizons.